Colorectal resection in emergency general surgery: An EAST multicenter trial. Issue 6 (December 2020) - Aicher, Brittany O.; Hernandez, Matthew C.; Betancourt-Ramirez, Alejandro; Grossman, Michael D.; Heise, Holly; Schroeppel, Thomas J.; Kongkaewpaisan, Napaporn; Kaafarani, Haytham M.A.; Wagner, Afton; Grabo, Daniel; Scott, Michael; Peck, Gregory; et al.
Abstract : OBJECTIVE: Evidence comparing stoma creation (STM) versus anastomosis after urgent or emergent colorectal resection is limited. This study examined outcomes after colorectal resection in emergency general surgery patients. METHODS: This was an Eastern Association for the Surgery of Trauma-sponsored prospective observational multicenter study of patients undergoing urgent/emergent colorectal resection. Twenty-one centers enrolled patients for 11 months. Preoperative, intraoperative, and postoperative variables were recorded. χ 2, Mann-Whitney U test, and multivariable logistic regression models were used to describe outcomes and risk factors for surgical complication/mortality. RESULTS: A total of 439 patients were enrolled (ANST, 184; STM, 255). The median (interquartile range) age was 62 (53–71) years, and the median Charlson Comorbidity Index (CCI) was 4 (1–6). The most common indication for surgery was diverticulitis (28%). Stoma group was older (64 vs. 58 years, p < 0.001), had a higher CCI, and were more likely to be immunosuppressed. Preoperatively, STM patients were more likely to be intubated (57 vs. 15, p < 0.001), on vasopressors (61 vs. 13, p < 0.001), have pneumoperitoneum (131 vs. 41, p < 0.001) or fecal contamination (114 vs. 33, p < 0.001), and had a higher incidence of elevated lactate (149 vs. 67, p < 0.001). Overall mortality was 13%, which was higher in STM patients (18% vs. 8%, p = 0.02). Surgical complications were more common in STM patients (35% vs. 25%, p = 0.02). On multivariable analysis, management with an open abdomen, intraoperative blood transfusion, and larger hospital size were associated with development of a surgical complication, while CCI, preoperative vasopressor use, steroid use, open abdomen, and intraoperative blood transfusion were independently associated with mortality. CONCLUSION: This study highlights a tendency to perform fecal diversion in patients who are acutely ill at presentation. There is a higher morbidity and mortality rate in STM patients. Independent predictors of mortality include CCI, preoperative vasopressor use, steroid use, open abdomen, and intraoperative blood transfusion. Following adjustment by clinical factors, method of colon management was not associated with surgical complications or mortality. LEVEL OF EVIDENCE: Therapeutic study, level IV. Abstract : Supplemental digital content is available in the text.